Sexual Dimorphism in Apical Periodontitis Severity Detected by CBCT - Estrela, Lucas Rodrigues de Araújo [UNESP]; Estrela, Carlos; Bueno, Mike R; Diogenes, Anibal (Elsevier, 2025)
INTRODUCTION: Although several elegant studies have reported apical periodontitis prevalence in different populations, far less is known about its associated bone loss and its correlation to sex and age. Thus, this study investigated the impact of sex and age differences on the severity of apical periodontitis (AP) using cone-beam computed tomography (CBCT) and a volumetric periapical index (CBCT-PAI). METHODS: CBCT scans of 401 patients (1,027 teeth) were analyzed by calibrated examiners in CBCT-PAI. Chi-square tests were used to assess associations between AP, sex, and age with other variables such as the presence and quality of endodontic treatment and coronal restorations. Robust Poisson regression models were used to evaluate the relationships between dependent and independent variables, with significance set at P < .05. RESULTS: The prevalence of AP was greater in female patients compared to males (66.9% vs 33.1%). Notably, men showed a significantly higher prevalence of larger lesions (CBCT-PAI 4 and 5) than women. Apical periodontitis was more common in root-filled teeth than primary infections, particularly posterior teeth. Lastly, AP was more commonly found in teeth with inadequate root canal fill or coronal restoration, while an intracanal post did not affect its prevalence. CONCLUSIONS: AP was more common in women. However, the osteolytic lesions in females were smaller than those seen in males, who demonstrated a greater prevalence of severe lesions. These findings emphasize the importance of early diagnosis and treatment and highlight the significant sexual dimorphism in the pathophysiology of AP.